A projective group study with alcohol dependent in-patients - Demirbaş, Hatice; Doğan, Yıldırım B. (Journal of Dependence, 2002)
Art therapy is a generic name for a wide spectrum of activities used in different clinical approaches. Despite the title, an expectation of literally artistic performance is quite uncommon. This paper deals with the issue of art therapy on the basis of an integrative group model designed mainly for alcohol inpatients. As a part of this model, drawing pictures constructs a considerable component of interactional process. In order to give an idea how precise data provided by this activity the drawings of two cases, one has dropped and the other one has completed the therapy, were compared and interpreted in this paper.
Keywords: Art therapy; interactional group; alcohol dependency